2021
DOI: 10.1186/s12966-021-01156-1
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity activity is more strongly associated with metabolic health in children compared to sedentary time: a cross-sectional study of the I.Family cohort

Abstract: Background Physical activity (PA) during childhood is important for preventing future metabolic syndrome (MetS). To examine the relationship between PA and MetS in more detail, accurate measures of PA are needed. Previous studies have only utilized a small part of the information available from accelerometer measured PA. This study investigated the association between measured PA and MetS in children with a new method for data processing and analyses that enable more detailed interpretation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
2
14
0
1
Order By: Relevance
“…The results of the presented mutually adjusted model of correlations between movement-related behaviors and the dichotomous diagnosis of the MetS are also in line with a recent meta-analysis showing that PA of at least moderate intensity, but not SED time, was independently associated with the presence of the MetS defined with dichotomous criteria in children and adolescents [ 18 ]. For Fridolfsson et al, the association between SED time and cardiometabolic health is generally weaker in contrast to high-intensity PA in youths [ 46 ]. However, the independence of the associations between movement-related behaviors and obesity-related health parameters remains debatable [ 18 , 23 , 46 , 47 , 48 ], as some recent longitudinal studies have reported significant positive associations between SED behaviors, BMI and fat mass index during childhood and adolescence, even after adjustment for MVPA [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the presented mutually adjusted model of correlations between movement-related behaviors and the dichotomous diagnosis of the MetS are also in line with a recent meta-analysis showing that PA of at least moderate intensity, but not SED time, was independently associated with the presence of the MetS defined with dichotomous criteria in children and adolescents [ 18 ]. For Fridolfsson et al, the association between SED time and cardiometabolic health is generally weaker in contrast to high-intensity PA in youths [ 46 ]. However, the independence of the associations between movement-related behaviors and obesity-related health parameters remains debatable [ 18 , 23 , 46 , 47 , 48 ], as some recent longitudinal studies have reported significant positive associations between SED behaviors, BMI and fat mass index during childhood and adolescence, even after adjustment for MVPA [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…For Fridolfsson et al, the association between SED time and cardiometabolic health is generally weaker in contrast to high-intensity PA in youths [ 46 ]. However, the independence of the associations between movement-related behaviors and obesity-related health parameters remains debatable [ 18 , 23 , 46 , 47 , 48 ], as some recent longitudinal studies have reported significant positive associations between SED behaviors, BMI and fat mass index during childhood and adolescence, even after adjustment for MVPA [ 47 , 48 ]. In the present study, the independence of the association between SED time and the continuous z-score of cardiometabolic risks is in line with these last results [ 47 , 48 ] and highlights the importance of reducing SED time in order to improve cardiometabolic health in adolescents with obesity, whatever the level of MVPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight loss is an effective strategy for reducing cardiometabolic risk in children with metabolic syndrome. Physical activity, which has attracted increasing amount of attention, can not only effectively reduce weight but also improve cardiometabolic health and increase cardiovascular fitness (Dias et al, 2018;Hansen et al, 2018;Labayen et al, 2020;Fridolfsson et al, 2021). A randomized controlled trial by Davis et al also showed that moderate-intensity aerobic exercise (heart rate approximately 150 beats/min) reduced body composition and the risk of diabetes effectively and improved glucose metabolism in overweight and obese children (Davis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Недавние исследования подтвердили, что любые упражнения, будь то аэробные, силовые или смешанные, в равной степени полезны, но нагрузки большей интенсивности не только позволяют снизить АД, но и способствуют уменьшению частоты регистрации метаболических факторов риска [31].…”
Section: обзор литературыunclassified